AmpliconDesign: an interactive web server for the design of high-throughput targeted DNA methylation assays - Schönung, Maximilian; Hess, Jana; Bawidamann, Pascal; Stäble, Sina; Hey, Joschka; Langstein, Jens; Assenov, Yassen; Weichenhan, Dieter; Lutsik, Pavlo; Lipka, Daniel (Epigenetics, 2021)
Targeted analysis of DNA methylation patterns based on bisulfite-treated genomic DNA (BT-DNA) is considered as a gold-standard for epigenetic biomarker development. Existing software tools facilitate primer design, primer quality control or visualization of primer localization. However, high-throughput design of primers for BT-DNA amplification is hampered by limits in throughput and functionality of existing tools, requiring users to repeatedly perform specific tasks manually. Consequently, the design of PCR primers for BT-DNA remains a tedious and time-consuming process. To bridge this gap, we developed AmpliconDesign, a webserver providing a scalable and user-friendly platform for the design and analysis of targeted DNA methylation studies based on BT-DNA, e.g. deep amplicon bisulfite sequencing (ampBS-seq) or EpiTYPER MassArray. Core functionality of the web server includes high-throughput primer design and binding site validation based on in silico bisulfite-converted DNA sequences, prediction of fragmentation patterns for EpiTYPER MassArray, an interactive quality control as well as a streamlined analysis workflow for ampBS-seq.